A therapeutic trial of milacemide in myoclonus and the stiff-person syndrome. - Brown, P; Thompson, P; Rothwell, J; Day, B; Marsden, C (1991)
We investigated the therapeutic effects of milacemide in seven patients with myoclonus and three patients with the stiff-person syndrome in an open-label trial. Milacemide was initiated at 800 mg/day and was gradually increased to a maximum dosage of 2,400 mg/day. No significant improvement occurred in the 10 patients.